Clinical Significance of mTOR and eIF4E Expression in Invasive Ductal Carcinoma. Issue 5 (September 2014) - Hu, Aixia; Sun, Miaomiao; Yan, Dong; Chen, Kuisheng
Aims and Background: Mammalian target of rapamycin (mTOR) is one of the serinethreonine protein kinases and plays an important regulatory role in cell growth. Eukaryotic translation initiation factor 4E (eIF4E) and 4E binding protein (4EBP) are the downstream proteins of mTOR signaling pathway and are the most efficient speed regulator of eukaryotic mRNA translation. The aim of the study was to investigate the clinical significance of mTOR, eIF4E and 4EBPs expression in invasive ductal carcinoma. Methods: Fresh biopsy specimens of invasive ductal carcinoma tissues and normal breast tissues were collected from 45 patients with breast cancer. The expressions of mTOR, eIF4E and 4EBPs in specimens were detected by an immunohistochemical SP method, and the relationship of mTOR, eIF4E and 4EBPS expressions and of their expressions with tumor metastasis were analyzed. Results: Expressions of mTOR, eIF4E and 4EBPs in invasive ductal carcinoma were significantly higher than in normal breast tissue (P <0.05). mTOR expression was positively correlated with eIF4E and 4EBP expression in invasive ductal carcinoma (P <0.05). The positive rates of mTOR, eIF4E and 4EBPs in patients with lymph node metastasis were significantly higher than in patients without lymph node metastasis (P <0.05). Conclusions: Increased expressions of mTOR and eIF4E in invasive ductal carcinoma may be correlated with the occurrence and metastasis of breast cancer.